Modified Negative Pressure Wound Therapy (Modified NPWT): An experience of 128 cases - Ranjeet, N; Dy, AU (Nepal Journal of Medical Sciences, 2012)
Background: Negative Pressure Wound Therapy (NPWT) or Vacuum Assisted Closure (VAC) is a method used to cover large wounds, decubitus ulcers and open fractures which cannot be closed either primarily or secondarily and which often requires skin graft or flaps or complex reconstructive procedure to cover the wound. Methods: We applied our modification of NPWT in 128 patients on large wounds, neglected wounds, large decubitus ulcers, fasciotomies and open fractures. Compared to the patented VAC system, our modification included presterilized foam, Saran® wrap or Glad® wrap, infant feeding tube or a nasogastric tube and bed side suction machine. Results: Majority of our cases were from open fractures. There were 98 cases of large soft tissue wounds, 3 cases of fasciotomies for compartment syndrome, 7 cases of peri-operative trauma infections, 16 cases of diabetic wounds and 4 decubitus ulcers. In our study, the average number of modified NPWT changes is 3 to 4, average number of days between modified NPWT changes is 3 to 5 days, and length of time modified NPWT applied before closure is 14 to 21 days. Most frequent mode of coverage is Split Thickness Skin Graft obviating the need of more complex flaps and microvascular reconstructive procedures. Conclusion: Our modifications are not inferior to the patented VAC but works just as well. The costs of our modifications are much less than the patented VAC, which is economical for our setting. DOI: http://dx.doi.org/10.3126/njms.v1i2.6610 Nepal Journal of Medical Sciences. 2012;1(2): 108-14